1996
DOI: 10.1016/s1074-7613(00)80269-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective Defects in the Development of the Fetal and Adult Lymphoid System in Mice with an Ikaros Null Mutation

Abstract: Mice homozygous for an Ikaros null mutation display distinct defects in the development of fetal and adult lymphocytes. Fetal T lymphocytes, and fetal and adult B lymphocytes and their earliest progenitors are absent. Postnatally, hematopoietic stem cells give rise to thymocyte precursors that undergo aberrant differentiation into the CD4 lineage and clonal expansion. The lack of NK cells and some gamma delta T cell subsets and a large reduction in thymic dendritic APCs suggest that Ikaros is essential for est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
553
2
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(575 citation statements)
references
References 0 publications
16
553
2
2
Order By: Relevance
“…Additionally, leukemogenesis induced by Ikaros deficiency is similar in phenotype to that induced by constitutively active Notch1. 33,47,48 Kathrein et al 41 contended that Ikaros deficiency results in de-repression of Hes1 in vivo and calculated that activating mutations of Notch1 in Ikaros-deficient cells further increase the expression of Hes1. In our study, the Hes1 level in TLs with mutations in both Ikaros and Notch1 was increased significantly compared to TLs harboring either mutation alone, suggesting that cooperative mutations advance Notch signaling via Hes1.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, leukemogenesis induced by Ikaros deficiency is similar in phenotype to that induced by constitutively active Notch1. 33,47,48 Kathrein et al 41 contended that Ikaros deficiency results in de-repression of Hes1 in vivo and calculated that activating mutations of Notch1 in Ikaros-deficient cells further increase the expression of Hes1. In our study, the Hes1 level in TLs with mutations in both Ikaros and Notch1 was increased significantly compared to TLs harboring either mutation alone, suggesting that cooperative mutations advance Notch signaling via Hes1.…”
Section: Discussionmentioning
confidence: 99%
“…Ikaros had been previously targeted and analysis of a null allele, a hypomorphic allele, and a dominant negative allele had shown that Ikaros was involved in lymphocyte, B cell, and natural killer cell development (Georgopoulos et al, 1994;Wang et al, 1996;Kirstetter et al, 2002). The ENU-induced allele, Ikaros plastic , showed defects in the formation of additional blood cell types including erythrocytes, granulocytes, and macrophages.…”
Section: Types Of Mutations and Allelic Seriesmentioning
confidence: 99%
“…In addition to defects in B cell development, Ik-null and Ik L/L mice develop T cell leukemia with 100% penetrance [1,2]. This phenotype is also observed in a third genetically engineered Ikaros mutant mouse line in which targeted deletion of exons 3 and 4 of the Ikaros gene results in high-level expression of non-DNAbinding Ikaros proteins from the targeted allele [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed at high levels at all stages of B cell development as well as in the mature B cell, providing circumstantial evidence that it plays a role in regulation of mature B cell function. Mice engineered to lack Ikaros (Ik-null mice) display a complete block in B cell development, making study of the role of Ikaros in B cell development and function difficult to impossible in this system [1]. In a second genetically engineered line of mice, Ik L/L mice, a b-galactosidase reporter gene was inserted into exon 2 of the Ikaros locus [2].…”
Section: Introductionmentioning
confidence: 99%